Estudio de ingeniería para la automatización del área de bomba de agua número 1 de la CELEC EP TERMOESMERALDAS I - García Arcentales, John Jairo (2017)
The work of qualifications " engineer's Study for the automation of the system of bombs N°1 CELEC EP TERMOESMERALDAS 1 " is a work for research that seeks to give clear and precise solutions to an ambiguous system of monitoring, supervision and control with which it counts the system of bombs, which to worked from approximately 20 years without no improvement realize, of such a form causes diverse difficulties on the part of the personnel entrusted to work in the above mentioned area one of the mistakes is the check of information inside the panel of monitoring. This panel possesses a set of elements of instrumentation that they must be checked constant to check its correct functioning, many of these must be replaced for new equipments, those that Many of these must be replaced by them for new equipments, those that, to the being different in its physical form, its new assembly impedes in the panel of monitoring, these possess different units from measure in much of the cases. However, develop a set of interactive screens towards the operators who offer the possibility of giving solutions to the system of current monitoring. That one allows to eliminate inconvenient sayings before detailed and to solve new worries discovered during the process for research. The installation of a PLC with a HMI like more viable solutions to the system of bombs makes necessary the reinstatement of the current elements of instrumentation for elements of ranges of measures from 4 to 20 mA and the development of electrical planes and of P&ID that offer the facility towards the personnel in charge of the installation.